Canto general e Latinomérica : da geografia à história, das pátrias à transnação - Santos, Éverton de Jesus (2021)
“Amor América (1400)”, first poem by Canto general (1950), an epic poem written by the Chilean Pablo Neruda, symbolically links the American being with love; “PátriAmérica”, on the other hand, a poem located in the middle of Latinomérica (2001), by the Brazilian Marcus Accioly, is a declaration of the American continent as one integrated homeland. Both works centralize the story in Latin America, treating it as a community and establishing dialogues between their countries; thus, starting from this perception, this thesis aims to study the constitution of its corpora considering both geographical and historical contents, through categories, elements and number of occurrences, in order to arrive at identity traits indicative of the existence of a Latin American transnation, in which the perspective of openness and enlargement, as well as union and sharing, goes beyond national borders. Therefore, Comparative Literature was established as a theoretical and critical field, because cultural relations in Latin America have been expanded by comparativism, and promoting dialogue between epic poems is part of the scope of this study; in addition, as methodological procedures characterized as pure basic, with qualitative and quantitative focus and exploratory objective, the following were adopted: searches for materials – books and academic texts – on the internet about poems, poets and themes related to the epic poetry; readings of the epics, mapping and calculation of the number of referents, with the subsequent division into categories and the production of tables; besides to the study of cutouts – verses and stanzas – from a raised framework. The elaboration of the analyzes demanded the use of references from different theoretical and critical aspects and areas of knowledge, such as Geography, History, Social Sciences, with a focus on Latin American scholars and intellectuals, privileging a locus of enunciation literarily constructed in the region; in addition, , historical and cultural approaches of Latin America and Brazil as texts on conquest, colonization, the invention of the continent, miscegenation, dictatorships, underdevelopment, integration, and, of course, literature and others themes. It was possible, through the operationalization of concepts such as identity, transnation, epos, heroism and anti-heroism, Pátria Grande, cosmic race, people, to create a representation of Latin Americanity as a symbolic system that, in Canto general and Latinomérica, is mobilized to establish identification between countries based on the sharing of common historical realities (such as the conquest, the colonial system and the military regimes) and geographical contiguity, as also the inversion between the position of the losers and winners of official History, in a revisionism that puts those in evidence, especially individualized heroes and the people, the collective subject/hero, to whom poets, transfigured into the I-lyrical/narrators, listen and for whom they speak. With this, the character of struggle, resistance and hope stands out, which leads to think Latin America, from Neruda and Accioly, as a union of nations, but, above all, as a single motherland, a transnation, which, in addition to of the integration projects, it is expressed by the sign of geo-historical unity in the two epic poems, so our contribution towards valuing both the epic genre and the inter-American relations through Literature.